Changing horizons in the 21st century perspectives on ageing - Phelan, Amanda (Cambridge Scholars Publishing, 2020)
The twenty-first century presents a changing global demographic. People are living longer and older people comprise a continued greater representation in populations. This book provides detailed insights into ageing issues related to longitudinal studies, legislation, policy, and the ageing experience (including a personal reflection on ageing), as well as ageing and the environment, intergenerational relations, ageivism and age representations in media. Consequently, the reader will benefit from a more complete, holistic understanding of ageing which will enhance their interactions with older.